Investigation on electrochemical properties of carbon nanotubes-graphite composite as anode material in lithium ion battery / Dzulieza Halib - Halib, Dzulieza (2008)
CNTs-graphite composite is used as an active anode material in lithium ion battery. The electrochemical properties of the anode material are characterized by variety of techniques. A literature review summarizes the findings of anode, cathode and electrolyte materials in lithium ion battery. The composite is prepared by method of ball milling. For battery fabrication, we use a method of coin cell assembly. A few apparatus and techniques need to be operated in order to determine the electrochemical characteristic of the composite including the cyclic voltammetry and charge discharge cycle. This composite shows a good cycling performance with also good cycle ability. Almost all the samples showed the capacity at the first cycle of 400 mAh/g. However, the average capacity is quite low while the capacity lost was a bit high.